The Effect of Corporation Reputation Mediation on Enterprise Risk Management (ERM) Disclosure and Firm Value - Firdausiyah, Zakiyah Fitri; Utami, Helianti; Sudarto, Triadi Agung (Journal of Applied Business, Taxation and Economics Research, 2024)
Enterprise Risk Management (ERM) disclosure can support companies to assess various threats and opportunities to maintain the firm's competitive advantage. The aim of this research is to analyze the effect of Enterprise Risk Management (ERM) disclosure on firm value with corporate reputation as a moderating variable. The research method used is an explanatory descriptive quantitative approach. The sample population for this research is manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2018-2021. The sampling technique used was purposive sampling, so that 38 companies were obtained. Data analysis techniques use inner model, outer model and hypothesis testing with the help of SmartPLS 4.0.9.5 software. The research results show that Enterprise Risk Management (ERM) disclosure and corporate reputation have a positive and significant effect on firm value. Corporate reputation has a positive and significant effect in mediating Enterprise Risk Management (ERM) disclosure on firm value. This research also uses profitability and firm size as control variables. The results of profitability research do not have a positive effect on firm value. Firm size has a positive effect on firm value. Recommendations for further research are to expand the variables used, such as corporate social responsibility, intellectual capital, corporate governance structure.